Kejadian Transmisi Vertikal Covid-19 Berdasarkan Jenis Persalinan - Shinta Mourinda Rachmani; Maya Tejasari; Winni Maharani Mauliani (UNISBA Press, 2024)
Abstract. The incidence of COVID-19 has been increasing since its emergence at the end of 2019 in the city of Wuhan, China, eventually developing into a pandemic. Pregnant women are a susceptible group to COVID-19. Pregnant women diagnosed with COVID-19 can transmit the virus to their unborn babies through vertical transmission, which can occur through three mechanisms: antepartum, intrapartum, and postpartum. This study aims to investigate the comparison of vertical transmission of COVID-19 between groups of mothers delivering spontaneously and through cesarean section at Al Ihsan Regional General Hospital in West Java Province. The observational study employs a population-based study design with medical record with a total of 122 pregnant women diagnosed with COVID-19 who gave birth at Al Ihsan Regional General Hospital in West Java Province. Data analysis is conducted using the Chi-Square test. The results indicate that there is no significant difference in vertical transmission of COVID-19 between the group of mothers delivering spontaneously and through cesarean section (p-value> 0.05). The low incidence of vertical transmission in six babies born spontaneously and seven babies born through cesarean section suggests that the placenta acts as a barrier effectively, and the low number of ACE receptors in reproductive organs causes vertical transmission not to occur always. Abstrak. Angka kejadian COVID-19 semakin meningkat sejak kemunculannya pada akhir 2019 di kota Wuhan, China, dan akhirnya berkembang menjadi pandemik. Ibu hamil merupakan kelompok yang rentan terhadap COVID-19. Ibu hamil yang didiagnosis COVID-19 dapat menularkan virus tersebut kepada bayi yang dikandungnya melalui transmisi vertikal, yang dapat terjadi melalui tiga mekanisme: antepartum, intrapartum, dan postpartum. Penelitian ini bertujuan untuk menyelidiki perbandingan transmisi vertikal COVID-19 antara kelompok ibu yang melahirkan secara spontan dan melalui operasi caesarea di RSUD Al Ihsan Provinsi Jawa Barat tahun 2020-2021. Penelitian observasional ini menggunakan desain studi berbasis populasi data diambil dari rekam medis dengan total 122 ibu hamil yang didiagnosis COVID-19 yang melahirkan di RSUD Al Ihsan Provinsi Jawa Barat. Analisis data dilakukan dengan uji Chi-Square. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan yang signifikan dalam transmisi vertikal COVID-19 antara kelompok ibu yang melahirkan secara spontan dan melalui operasi caesarea (p-value > 0,05). Rendahnya kejadian transmisi vertikal pada enam bayi yang lahir secara spontan dan tujuh bayi yang lahir melalui operasi caesarea menunjukkan bahwa plasenta berfungsi sebagai penghalang dengan efektif, dan jumlah reseptor ACE yang rendah pada organ reproduksi menyebabkan transmisi vertikal tidak selalu terjadi.